Behaviour of a self-reinforced polylactic acid (SRPLA) in seawater. (July 2022) - Le Gall, M.; Niu, Z.; Curto, M.; Catarino, A.I.; Demeyer, E.; Jiang, C.; Dhakal, H.; Everaert, G.; Davies, P.
Abstract: The goal of this study was to determine whether a bio-based self-reinforced polylactic acid (SRPLA) is suitable for use in structures deployed in the marine environment. The material was produced from co-mingled fibres with different melting points. Two key criteria, durability during service and microplastic formation, were examined. To assess durability, mechanical properties, tension and transverse impact, were used to quantify the influence of seawater ageing for up to 24 months. After seawater ageing at 40 °C for 12 months, composite strength was completely degraded. To assess microplastic formation, specimens of SRPLA were exposed in seawater to accelerated ultraviolet (UV) radiation simulating natural exposure for up to 18 months. Fluorescence microscopy and infrared technology were used to quantify and characterise the microplastics formed. Their number was independent of UV exposure, suggesting short-term UV radiation does not accelerate SRPLA microplastic formation. We discuss the potential for SRPLA to be considered a promising material for sustainable marine applications. Highlights: New test results are shown for seawater aging of SRPLA for up to 24 months' immersion. Correlation established between water ingress and property loss. Tensile and impact test results show PLA ductility can be improved by self-reinforcement. Study of microplastic formation in seawater with and without UV exposure.